Comparative transcriptome analysis of gynoecious and monoecious inflorescences reveals regulators involved in male flower development in the woody perennial plant Jatropha curcas - Mei-Li Zhao; Mao-Sheng Chen; Jun Ni; Chuan-Jia Xu; Qing Yang; Zeng-Fu Xu (Plant Reproduction, 2020)

Developmental basis for flower sex determination and effects of cytokinin on sex determination in Plukenetia volubilis (Euphorbiaceae) - Yan Luo; Bang-Zhen Pan; Lu Li; Chen-Xuan Yang; Zeng-Fu Xu (Plant Reproduction, 2020)
Key message Cytokinin might be an important factor to regulate floral sex at the very early stage of flower development in sacha inchi. Abstract Sacha inchi ( Plukenetia volubilis , Euphorbiaceae) is characterized by having female and male flowers in a thyrse with particular differences. The mechanisms involved in the development of unisexual flowers are very poorly understood. In this study, the inflorescence and flower development of P. volubilis were investigated using light microscopy and scanning electron microscopy. We also investigated the effects of cytokinin on flower sex determination by exogenous application of 6-benzyladenine (BA) in P. volubilis . The floral development of P. volubilis was divided into eight stages, and the first morphological divergence between the male and female flowers was found to occur at stage 3. Both female and male flowers can be structurally distinguished by differences in the shape and size of the flower apex after sepal primordia initiation. There are no traces of gynoecia in male flowers or of androecia in female flowers. Exogenous application of BA effectively induced gynoecium primordia initiation and female flower development, especially at the early flower developmental stages. We propose that flower sex is determined earlier and probably occurs before flower initiation, either prior to or at inflorescence development due to the difference in the position of the female and male primordia in the inflorescence and in the time of the female and male primordia being initiated. The influence of cytokinin on female primordia during flower development in P. volubilis strongly suggests a feminization role for cytokinin in sex determination. These results indicate that cytokinin could modify the fate of the apical meristem of male flower and promote the formation of carpel primordia in P. volubilis.